2007
DOI: 10.1123/ijspp.2.2.128
|View full text |Cite
|
Sign up to set email alerts
|

VO2 Attained During Treadmill Running: The Influence of a Specialist (400-m or 800-m) Event

Abstract: Purpose:Previously it has been observed that, in well-trained 800-m athletes, VO2max is not attained during middle-distance running events on a treadmill, even when a race-type pacing strategy is adopted. Therefore, the authors investigated whether specialization in a particular running distance (400-m or 800-m) influences the VO2 attained during running on a treadmill.Methods:Six 400-m and six 800-m running specialists participated in the study. A 400-m trial and a progressive test to determine VO2max were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…If VO 2max is not attained in middle‐distance treadmill running at constant pace, this may have important implications for understanding the energetics of these events. Recently, it has been shown that the warm‐up strategy, pacing strategy, V O 2max , and specialist event of the athlete appears to influence the V O 2 attained during treadmill running (Draper, Wood, Corbett, James, & Potter, 2007; James, Sandals, Draper, Maldonado‐Martin, & Wood, 2007a; James et al ., 2007b; Sandals et al ., 2006), although a shortfall in V O 2 attained still remained. To what extent the V O 2 attained is a function of the duration of the event remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…If VO 2max is not attained in middle‐distance treadmill running at constant pace, this may have important implications for understanding the energetics of these events. Recently, it has been shown that the warm‐up strategy, pacing strategy, V O 2max , and specialist event of the athlete appears to influence the V O 2 attained during treadmill running (Draper, Wood, Corbett, James, & Potter, 2007; James, Sandals, Draper, Maldonado‐Martin, & Wood, 2007a; James et al ., 2007b; Sandals et al ., 2006), although a shortfall in V O 2 attained still remained. To what extent the V O 2 attained is a function of the duration of the event remains an open question.…”
Section: Introductionmentioning
confidence: 99%